Human machine interface design analysis of defect detection prototype by wonderware intouch software - Tatang, Mulyana; Ibrahim, Rasidi; Abd Rahim, Erween (IOP Publishing, 2019)
Human Machine Interface (HMI) serves as a bridge for operators to understand the processes that occur on the machine. Without HMI, operators will have difficulty in monitoring and controlling the machine. HMI used in this study using Wonderware InTouch software. The HMI design that is used, displays the home button, as the start screen. There are two options in the home menu, which is the option to login as an identification and classification operator. To start operation and enter the monitoring window, any operator that uses this HMI must login using a username and password. The function of HMI in this research is as a connector between operators with machine. In this paper we have presented the human machine interface design of defect detection prototype by wonderware intouch software. Based on the tested results can be concluded that the designed is successfully.